1997
DOI: 10.1152/ajpheart.1997.273.6.h2575
|View full text |Cite
|
Sign up to set email alerts
|

Induction of nitric oxide synthase mRNA in coronary resistance arteries isolated from exercise-trained pigs

Abstract: The purpose of this study was to develop a method by which endothelial cell nitric oxide synthase (ecNOS) mRNA expression could be measured in single coronary resistance arteries and to test the hypothesis that ecNOS gene expression is upregulated by exercise training. Yucatan miniature swine were randomly assigned to exercise-trained (ET; n = 5) or sedentary (Sed; n = 4) groups for 16 wk. Individual coronary resistance arteries (50–100 μm) were dissected, frozen in liquid nitrogen, and homogenized in a LiCl b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
124
2
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(142 citation statements)
references
References 11 publications
15
124
2
1
Order By: Relevance
“…These results are consistent with other studies that have reported elevated NOS mRNA levels in aortas of exercise-trained dogs, and in coronary resistance vessels of exercise-trained pigs (38,39). The expression of inducible NOS and endothelial NOS mRNA was increased in endothelial cells by chronic treadmill training, whereas chronic exercise blunted phenylephrine-induced vascular responses, probably by increasing nitric oxide release via inducible NOS in the rat thoracic aorta (40).…”
Section: Impact Of Different Risk Factors In Combination On the Cardisupporting
confidence: 92%
“…These results are consistent with other studies that have reported elevated NOS mRNA levels in aortas of exercise-trained dogs, and in coronary resistance vessels of exercise-trained pigs (38,39). The expression of inducible NOS and endothelial NOS mRNA was increased in endothelial cells by chronic treadmill training, whereas chronic exercise blunted phenylephrine-induced vascular responses, probably by increasing nitric oxide release via inducible NOS in the rat thoracic aorta (40).…”
Section: Impact Of Different Risk Factors In Combination On the Cardisupporting
confidence: 92%
“…Relative differences in eNOS and SOD-1 mRNA expression in single feed arteries were assessed as described previously (26,28). Briefly, single feed arteries were homogenized in 50 l LiCl lysis buffer by vortexing the sample vigorously for 60 s. The sample was subsequently spun briefly in a microcentrifuge, and the process was repeated four to five times until the artery was completely digested.…”
Section: Quantification Of Enos and Sod-1 Expressionmentioning
confidence: 99%
“…Poly(A) ϩ RNA was isolated from the crude lysate with paramagnetic oligo(dT) beads (Dynal), and first-strand cDNA synthesis was performed in a 20-l volume (Superscript Preamplification System, GIBCO-BRL Life Technologies). Nine microliters of cDNA were used in a PCR using previously published primers and cycling conditions for eNOS or SOD-1 (26,28). The PCR consisted of 25 cycles to ensure that the reaction was within the linear range for the eNOS and SOD-1 primer sets.…”
Section: Quantification Of Enos and Sod-1 Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this concentration of ¬_NAME has been previously found to act as a muscarinic antagonist (see Buxton et al 1993). Exercise training has been reported to increase eNOS protein in the rat abdominal aorta (4 weeks of treadmill running; Delp & Laughlin, 1997) and in the canine aorta (10 days treadmill running; Sessa et al 1994), and to increase eNOS mRNA in the minipig coronary artery (16 weeks treadmill running, Woodman et al 1997). Therefore, in this present study the larger effect of ¬_NA on the ACh-relaxation of saphenous artery rings from trained animals may result from enhanced levels of NOS protein in this artery.…”
Section: Relaxation Responsesmentioning
confidence: 99%